Students’ Interest in Entrepreneurship After Following Entrepreneurship Practice of “Indonesian Traditional Snack Creation” - Nova Pratiwi; Januardi (NAROTAMA UNIVERSITY, Indonesia, 2020)
This research attempted to describe students' interest in entrepreneurship after following the entrepreneurship practice of